Direito à educação de pessoas com deficiência: um estudo a partir da análise das diretrizes e matrizes curriculares de cursos de Licenciatura em Educação Física - SANTOS, Evanir Sebastião dos (2022)
The study of guidelines and curriculum matrices aimed at undergraduate courses, specifically in the field of Physical Education, has had increasing importance and relevance in terms of the direct impact on the training process of teachers who work with people with disabilities, because the construction of a society what is said to be inclusive presupposes the guarantee of equal rights and the appreciation of diversity, aspects that this study proposes to investigate. Thus, in the light of considerations of the curriculum guidelines published in 2018 and the curriculum matrices of degree courses in Physical Education, from three Universities, the objective is to identify references and content related to the rights of people with disabilities, with a view to highlighting aspects related to the guiding principles of the inclusive process and the possible impacts on teacher education. The theoretical framework to support the present study draws on the contributions of Neira (2008, 2009, 2010, 2011, 2013, 2014) plus authors who are aligned with it, such as: Arelaro and Silva (2017); Arroyo (2013); Hashizume (2020); Fabris and Klein (2013); Lopes and Fabris (2017), among others. From the methodological point of view, it is a qualitative study of a descriptive nature that involves documentary research limited to the current curricular guidelines, as well as the analysis of curricular matrices of physical education degree courses, including the menus of three higher education institutions located in the ABCD region, in São Paulo. Regarding the results, the curricular components specifically aimed at dealing with issues related to inclusive practice in undergraduate courses, especially in the Physical Education course, are incipiently in the curriculum and do not ensure initial training that includes inclusive practices for the graduates. As for the conclusive aspects, it is evident that there is a distance from what HEIs offer, which is required in a modest way by legislation, from what would be ideal(AU)